2019
DOI: 10.1177/1045389x19873408
|View full text |Cite
|
Sign up to set email alerts
|

Seismic fragility analyses of steel building frames installed with superelastic shape memory alloy dampers: Comparison with yielding dampers

Abstract: Smart materials such as shape memory alloys have unique material properties that can potentially mitigate earthquake hazards on the built environment. Implementation of shape memory alloy-based devices on building structures should incorporate two key factors: (1) distinct mechanical features of the devices and (2) inherent large uncertainty stemming from material properties, building geometry, and ground motions. This study conducts seismic fragility analyses of steel building frames installed with superelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 57 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…However, modern models have been so far quite rarely used in structural control applications. Gur et al (2019) also report this. They use in their study the rate dependent model of Helm and Haupt (2003) to simulate SMA dampers in steel buildings.…”
Section: Introductionsupporting
confidence: 56%
“…However, modern models have been so far quite rarely used in structural control applications. Gur et al (2019) also report this. They use in their study the rate dependent model of Helm and Haupt (2003) to simulate SMA dampers in steel buildings.…”
Section: Introductionsupporting
confidence: 56%
“…The accuracy of the simplified approach is within 1% in comparison with the original Kingery results. Simplified Kingery Airblast Calculations approach recommended the following polynomial equation to determine the blast wave parameters, = [ + × (ln( )) + × (ln( )) 2 + × (ln( )) 3 + × (ln( )) 4 + × (ln( )) 5 + × (ln( )) 6 ]…”
Section: Modeling Of Blast Loadingmentioning
confidence: 99%
“…The study showed that joint configuration equipped with NiTi SMA bolts experienced a fully flag-shaped hysteresis loop. Recently, Gur et al examined the effect of SMA bars to improve the seismic performance of steel frames equipped with SMA dampers [4]. The study observed the novelty of SMA comparing with other damper models, e.g., yielding damper.…”
mentioning
confidence: 99%
“…Phase transformations provided by SMA can be enjoyed to reduce vibration with significant results. One of the approaches is to dissipate energy through a hysteretic phase transformation of its microstructure (Gur et al, 2016(Gur et al, , 2019Mishra et al, 2013;Savi et al, 2011). Assuming that SMA behavior is similar to a damper, through this strategy it leads to employment as tuned mass damper (SMA-TMD), reaching proper results (Mishra et al, 2013;Savi et al, 2011).…”
Section: Sma Concept Applied To Vibration Controlmentioning
confidence: 99%